Understanding bacterial adaptation to aerobic and anaerobic environments through experimental evolution and whole genome analysis : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Genetics at Massey University, Palmerston North, New Zealand - Finn, Thomas (Massey University, 2014)
Facultative anaerobic organisms have the metabolic versatility to grow in both aerobic and anaerobic environments. However, molecular mechanisms that underpin adaptation to anaerobic environments are not well understood. This study aims to understand how the facultative anaerobe, Escherichia coli, adapts to environments that vary in oxygen content. An experimental evolution experiment was conducted in which replicate lineages were established from a preevolved clonal culture of E. coli REL4536. Lineages were serially sub-cultured for 4,000 generations within strict aerobic and strict anaerobic environments, and a treatment that fluctuated between the two environments. Significant increases in the relative fitness of lineages exposed to anaerobic conditions were observed, whereas the relative fitness of lineages in aerobic conditions did not increase, likely as the ancestor had been pre-adapted to aerobic growth. Mutations that arose during evolution were identified by genome sequencing randomly-selected clones from each lineage at 2,000 and 4,000 generations. Traits that contributed to adaptation were predicted via the occurrence of independent mutations affecting common traits among lineages. Adaptation to the anaerobic environment was facilitated by modifications to anaerobic fermentation and the inactivation of virulence genes, whereas in the aerobic environment, mutations predicted to confer a growth advantage in stationary phase were observed. The evolution of generalists involved traits that were similar to those found in both aerobic and anaerobically evolved lineages, as well as the deletion of cryptic prophages from the genome and modifications to amino acid transport. Phenotypically distinct small colony morphotypes (SCM) arose within anaerobic lineages and two separate adaptive pathways are hypothesised for this divergence. SCM1 were capable of stable coexistence with co-evolved cells of typical colony morphotype, most likely through an acetate crossfeeding mechanism. In contrast, SCM2 was able to out-compete the ancestor within 14 days, despite exhibiting a lower growth rate than the ancestor. SCM2 likely evolved the ability to inhibit the ancestral strain through a contact dependent inhibition mechanism, as evidenced by a mutation in glgC. This thesis demonstrates the complex nature of adaptation to anaerobic environments, as revealed by experimental evolution and whole genome sequencing.
Keywords: Escherichia coli; Anaerobic bacteria; Genetics; Evolution; Adaptation; Research Subject Categories::NATURAL SCIENCES::Biology::Cell and molecular biology::Genetics